Educação ambiental e os componentes físico-naturais no ensino de Geografia: propostas de metodologias ativas nas 1º séries do Ensino Médio do Instituto Federal de Educação, Ciência e Tecnologia do Piauí, câmpus Oeiras - Santos, Anderson Felipe Leite dos [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Environmental Education is an absolutely crucial milestone in the development of citizenship. Considering this, it is necessary to consider schools as transformative spaces that foster sustainable attitudes for those involved in the teaching and learning process. Since Geography is responsible for reflecting on the relationship between society and nature from its various perspectives, the debate on Environmental Education is essential for fostering socio-environmental awareness among students from the earliest years of school. In this context, this research proposal aims to understand the potential of combining the Physical-Natural Components for the development of Critical Environmental Education in the didactic mediation of geographic knowledge in high school. To this end, a qualitative approach, an action-research methodology, is employed. Thus, 147 first-year high school students from the Federal Institute of Education, Science, and Technology of Piauí (IFPI), Oeiras Campus, entering in the first semester of 2024, were selected as research subjects. To achieve the proposed objectives, structured questionnaires were administered to the high school students participating in the research, in addition to theoretical and practical pedagogical approaches using active methodologies on topics related to the Physical-Natural Components in their interface with Environmental Education. As a result, it was found that the students engaged with great enthusiasm and dedication in the development of active methodologies encompassing the Physical-Natural Components in their interface with Environmental Education. It is noteworthy that it was essential to involve geographic principles and address the topics using a local scale. In this sense, although physical-natural themes have lost ground in the first year of high school due to the National Common Curricular Base (BNCC), including in textbooks based on it, the Geography teacher plays a fundamental role in developing the curriculum, using other teaching materials beyond the textbook. It can be concluded that high school in today's world is a challenge, due to the loss of workload and the unification of subjects and teaching materials designed to work interdisciplinarily within a given area of knowledge. Furthermore, given the many challenges faced, we sought to reframe the environmental debate in high school through active methodologies that enabled students to learn through their own actions.

Environmental Education is an absolutely crucial milestone in the development of citizenship. Considering this, it is necessary to consider schools as transformative spaces that foster sustainable attitudes for those involved in the teaching and learning process. Since Geography is responsible for reflecting on the relationship between society and nature from its various perspectives, the debate on Environmental Education is essential for fostering socio-environmental awareness among students from the earliest years of school. In this context, this research proposal aims to understand the potential of combining the Physical-Natural Components for the development of Critical Environmental Education in the didactic mediation of geographic knowledge in high school. To this end, a qualitative approach, an action-research methodology, is employed. Thus, 147 first-year high school students from the Federal Institute of Education, Science, and Technology of Piauí (IFPI), Oeiras Campus, entering in the first semester of 2024, were selected as research subjects. To achieve the proposed objectives, structured questionnaires were administered to the high school students participating in the research, in addition to theoretical and practical pedagogical approaches using active methodologies on topics related to the Physical-Natural Components in their interface with Environmental Education. As a result, it was found that the students engaged with great enthusiasm and dedication in the development of active methodologies encompassing the Physical-Natural Components in their interface with Environmental Education. It is noteworthy that it was essential to involve geographic principles and address the topics using a local scale. In this sense, although physical-natural themes have lost ground in the first year of high school due to the National Common Curricular Base (BNCC), including in textbooks based on it, the Geography teacher plays a fundamental role in developing the curriculum, using other teaching materials beyond the textbook. It can be concluded that high school in today's world is a challenge, due to the loss of workload and the unification of subjects and teaching materials designed to work interdisciplinarily within a given area of knowledge. Furthermore, given the many challenges faced, we sought to reframe the environmental debate in high school through active methodologies that enabled students to learn through their own actions.
Environmental education and the physical-natural components in the teaching of Geography: proposals for active methodologies in the 1st year of High School at the Federal Institute of Education, Science and Technology of Piauí, Oeiras campus
Keywords: EA crítica; Ensino Médio Técnico; Metodologias ativas; IF-Oeiras/PI; Critical Education; Technical High School; Active Methodologies; IF-Oieiras/PI